Implementasi Kurikulum Merdeka sebagai Wujud Nyata Visi Pendidikan IMTAQ, IPTEK, dan Karakter di SMA Yuppentek 1 Tangerang - Aelsya Amara Putri Alta; Siti Almiah Fathimatuzzahra; Syadela Syadela; Raenita Rifalina; Roiatul Jannah; Fika Nazila; Usman Usman (Sumule Indonesia Publishing, 2025)
This study aims to describe the implementation of the Merdeka Curriculum as a realization of an educational vision that integrates faith and devotion (IMTAQ), mastery of science and technology (IPTEK), and character development at SMA Yuppentek 1 Tangerang. A descriptive qualitative approach was employed, using data collection techniques such as observation, interviews, and documentation. The findings indicate that the Merdeka Curriculum was implemented through differentiated instruction, project-based learning, and authentic assessment. Supporting programs such as Baca Tulis Al-Qur’an (Qur’an Literacy), various extracurricular activities, and technology-based assessment systems contributed to the successful implementation. This curriculum application strengthened students’ religious values, technological skills, and social character in line with the Pancasila Student Profile. Moreover, integrating 21st-century skills (4Cs) and a holistic education approach fostered an active, collaborative, and reflective learning environment that prepared students to face global challenges.